Indigenous women and violence: feminist activist research in heightened states of injustice - Stephen, Lynn; Speed, Shannon (The University of Arizona Press, 2021)
"An intimate view of how inequality and deeply ingrained structural settler colonialism build accumulated violences in the lives of indigenous women and how these women resist"--